Uji daya hambat ekstrak bunga cengkeh (Syzygium aromaticum) terhadap bakteri Porphyromonas gingivalis - Paliling, Agrianto; Posangi, Jimmy; Anindita, P. S. (Universitas Sam Ratulangi, 2016)
Abstract: Cloves (Syzygium aromaticum) are commonly found in tropical territory. Flower bud of cloves contains cloves essential oil with its main compound is eugenol. Porphromonas gingivalis is an anaerob Gram negative bacterium which is one of the normal floras in oral cavity. However, it has the ability to cause an infection such as periodontitis. This study was aimed to determine the inhibition effect of cloves flower bud extract on Porphyromonas gingivalis growth through the diameter magnitude of the inhibition zone. The category of inhibition zone was based on Davis and Stout. This was an experimental study using Kirby-bauer modification method. Cloves flower bud samples were obtained from Senduk Tanawangko and were extracted with maseration method using etanol 96%. Porphyromonas gingivalis bacteria were obtained from pure bacteria stock in the Laboratory of Microbiology Faculty of Medicine, University of Hasanuddin Makassar. The results showed that the average diameter of inhibition zone of cloves flower bud extract against Porphyromonas gingivalis was 13.01 mm. Conclusion: Cloves flower bud extract had a strong ability to inhibit Porphyromonas gingivalis growth.Keywords: cloves flower bud, Porphyromonas gingivalis, inhibition zoneÂ Abstrak: Tanaman cengkeh (Syzygium aromaticum) merupakan tanaman yang banyak tumbuh di daerah beriklim tropis. Bunga cengkeh mengandung minyak atsiri (clove essential oil) dengan kandungan utama ialah eugenol. Porphyromonas gingivalis ialah bakteri anaerob Gram negatif yang merupakan salah satu bakteri flora normal dalam rongga mulut tetapi jika berlebihan dapat menyebabkan penyakit periodontitis. Penelitian ini bertujuan untuk mengetahui daya hambat ekstrak bunga cengkeh terhadap Porphyromonas gingivalis yang dinilai melalui besar diameter zona hambat yang terbentuk. Kategori daya hambat berdasarkan penggolongan Davis dan Stout. Jenis penelitian ialah eksperimental dengan metode modifikasi Kirby-Bauer menggunakan sumuran. Sampel bunga cengkeh diambil dari Desa Senduk Tanawangko kemudian diekstraksi dengan metode maserasi menggunakan pelarut etanol 96%. Bakteri Porphyromonas gingivalis diambil dari stok bakteri murni yang diperoleh dari Laboratorium Mikrobiologi Fakultas Kedokteran Universitas Hasanudin. Hasil penelitian mendapatkan nilai rerata diameter zona hambat ekstrak bunga cengkeh terhadap bakteri Porphyromonas gingivalis sebesar 13,01 mm. Simpulan: Ekstrak bunga cengkeh memiliki daya hambat kuat berdasarkan kategori Davis dan Stout terhadap bakteri Porphyromonas gingivalis. Kata kunci: bunga cengkeh, Porphyromonas gingivalis, zona hambat